(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
India,being a signatory of the WTO, has to reform agriculture sector to give marketaccess to other member countries. There is urgent need to prepare this sectorfor global competition. Now, agriculture should not be seen in the context offood security alone but as a multifunctional sector contributing to (a)national product (b) low inflation (c) alleviation of poverty (d) market forfarm input (e) savings to economic development (f) import substitute andforeign exchange earnings (g) releasing labour for other sectors (Desai, 99).To foster its competitiveness, agriculture sector needs to be liberated on theline of other manufacturing sectors being reformed to improve their competitivenessin globalized economy.